PIRPO: An Algorithm to deal with Polarity in Portuguese Online Reviews from the Accommodation Sector - Chaves, Marcirio (2012)
This paper presents the algorithm Polarity Recognizer in Portuguese (PIRPO) to classify sentiment in online reviews. PIRPO was constructed to identify polarity in Portuguese user-generated accommodation reviews. Each review is analysed according to concepts from a domain ontology. We decompose the review in sentences in order to assign a polarity to each concept of the ontology in the sentence. Preliminary results indicate an average F-score of 0.32 for polarity recognition.